Adaptation, Validity and Reliability of the Body Sensations Questionnaire Turkish Version - Aysegül KART; M. Hakan TÜRKÇAPAR (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: In this study, it is aimed to evaluate the validity and reliability of Body Sensations Questionnaire (BSQ). Method: BSQ was administered to 122 patients with panic disorder. BSQ Turkish version completed by translation, back-translation and pilot assessment. Socio-demographic Data Form and BSQ Turkish version were administered to participants. Construct validity was assesed by factor analysis after Kaiser-Meyer-Olkin (KMO) and Bartlett tests applied. Principal component analysis and varimax rotation used for factor analysis. Results: 66% (n=80) of the participants were female and 34% (n=42) were male. The mean age of participants was 31,7±10,8 years and age range was 18-58 years. Internal consistency of the questionnaire was calculated 0,921 by Cronbach alpha. In analysis performed by split-half method reliability coefficients of half questionnaire were found as 0,889 and 0,850. Again spearmen-brown coefficient was found as 0,849 by the same analysis. Factor analysis revealed five basic factors. 75,2% of the total variance was explained with these five factors. Conclusion: The results of this study show that the Turkish version of BSQ is a reliable and valid scale for measuring the fear of the bodily sensations associated with panic.